2009
DOI: 10.4103/1817-1737.56011
|View full text |Cite
|
Sign up to set email alerts
|

Autologous blood pleurodesis: A good choice in patients with persistent air leak

Abstract: AIM:The study compares the efficiency, side effects and complications of autologous blood pleurodesis with talcum powder and tetracycline.MATERIALS AND METHODS:This prospective study evaluated 50 patients with persistent air leak resulting from primary and secssondary spontaneous pneumothorax between February 2004 and March 2009. The patients inclussded 32 (64.0%) males and 18 (36.0%) females with a median age of 39 years (range 14-69 years). All cases had persistent air leak of more than seven days. Pleurodes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 21 publications
1
36
1
1
Order By: Relevance
“…To our knowledge, this study is among the largest (with 68 patients) to examine the experience with blood pleurodesis in patients with prolonged air leakage after lung resection. The success rate of the procedure was 67.6%, similar to previous reports [15,[20][21][22]. The main limitations of this study include its retrospective design and the lack of a control group for comparison.…”
Section: Discussionsupporting
confidence: 83%
“…To our knowledge, this study is among the largest (with 68 patients) to examine the experience with blood pleurodesis in patients with prolonged air leakage after lung resection. The success rate of the procedure was 67.6%, similar to previous reports [15,[20][21][22]. The main limitations of this study include its retrospective design and the lack of a control group for comparison.…”
Section: Discussionsupporting
confidence: 83%
“…Indeed, the rate of patients who required invasive procedures was higher in the present study (34%) than that reported in previous studies (3.8-20.4%) (9)(10)(11). Pneumothorax patients treated with a longer duration of chest tube drainage are reported to have a high risk for developing respiratory infection, empyema formation and deep venous thrombosis (7,8). We believe that our strategy, namely conversion to invasive procedures in pneumothorax patients with prolonged air leaks based on thoracographic findings, is therefore justified, considering the risks associated with longterm chest tube drainage.…”
Section: Discussioncontrasting
confidence: 50%
“…However, conversion to invasive procedures in pneumothorax patients with prolonged air leakage requires skilled clinical judgment. Pneumothorax may resolve spontaneously in a large proportion of patients, who do not require invasive procedures, while other pneumothorax patients have a high risk of respiratory infection, empyema formation and deep venous thrombosis due to the inappropriate use of VATS (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…Bu hasta grubunda tüp torakostomi uygulamasını takiben otolog kan, talk veya tetrasiklin gibi değişik ajanlar kullanılarak yapılan plörodez yöntemlerinde değişik başarı oranları elde edilmiştir. [15] Ayrıca göğüs cerrahisinde ameliyat sonrası hava kaçaklarını azaltmak için BioGlue ® (CryoLife Europa Ltd, Hampshire, United Kingdom), Peri-strips ® (Synovis Life Technologies Inc, St Paul MN, USA) ve Tachosil ® (Nycomed Pharma AS, Linz Austria) gibi doğal ve sentetik doku yapıştırıcıları kullanılarak farklı oranlarda başarılar elde edilmiştir. [3,16] Buna karşın Kawamura ve ark.…”
Section: Discussionunclassified